Initial Report of a Phase I Study of LY2510924, Idarubicin, and Cytarabine in Relapsed/Refractory Acute Myeloid Leukemia - Boddu, Prajwal; Borthakur, Gautam; Koneru, Mythili; Huang, Xuelin; Naqvi, Kiran; Wierda, William; Bose, Prithviraj; Jabbour, Elias; Estrov, Zeev; Burger, Jan; Alvarado, Yesid; Deshmukh, April; et al. (Frontiers in Oncology, 2018)
Background: The CXCR4/SDF-1α axis plays a vital role in the retention of stem cells within the bone marrow and downstream activation of cell survival signaling pathways. LY2510924, a second generation CXCR4, showed significant anti-leukemia activity in a murine AML model. Methods: We conducted a phase I study to determine the safety and toxicity of LY2510924, idarubicin and cytarabine (IA) combination therapy in relapsed/refractory (R/R) AML. Eligible patients were 18–70 years of age receiving up to salvage 3 therapy. A peripheral blood absolute blast count of < 20,000/μL was required for inclusion. LY2510924 was administered daily for 7 days followed by IA from day 8. Two dose escalation levels (10 and 20 mg) were evaluated, with a plan to enroll up to 12 patients in the phase I portion. Results: The median age of the enrolled patients (n = 11) was 55 years (range, 19–70). Median number of prior therapies was 1 (1–3). Six and five patients were treated at dose-levels “0” (10 mg) and “1” (20 mg), respectively. Only one patient experiencing a dose limiting toxicity (grade 3 rash and myelosuppression). Three and one complete responses were observed at dose-levels “0” and “1,” respectively; the overall response rate (ORR) was 36% (4 of 11 patients). A ≥ 50% decrease in CXCR4 mean fluorescence intensity was observed in 4 of 9 patients by flow cytometry, indicating incomplete suppression of CXCR4-receptor occupancy. Conclusions: The combination of LY2510924 with IA is safe in R/R AML. Dose-escalation to a 30 mg LY2510924 dose is planned to achieve complete blockade of CXCR4 receptor occupancy, followed by expansion phase at the recommended phase 2 dose-level.